2014
DOI: 10.1002/alr.21436
|View full text |Cite
|
Sign up to set email alerts
|

Verapamil modulates interleukin‐5 and interleukin‐6 secretion in organotypic human sinonasal polyp explants

Abstract: Although the mechanism has yet to be fully understood, L-type CCBs are capable of reducing inflammation in multiple tissues. Verapamil was specifically found to reduce airway goblet cell hyperplasia and eosinophilic infiltration in a murine asthma model. Our data support these findings suggesting that verapamil can modulate T-helper cell type 2 (Th2)-associated cytokine secretion in sinonasal polyp explants. This data points to a possible therapeutic role for CCBs in the management of CRSwNP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 21 publications
0
26
0
Order By: Relevance
“…3 The activities of nucleation-promoting factors for actin polymerization are mostly regulated by signaltransduction pathways, one of which involves the activation by the Rho-family guanosine triphosphatases CDC42 and RAC2, and the Wiskott-Aldrich Syndrome protein (WASP) family as the intermediary Arp2/3 activator that can control actin assembly downstream of these small guanosine triphosphatases. 4,5 Here we describe the first human genetic defect in a component of the Arp2/3 complex itself. The ARPC1B mutation results in a combined immunodeficiency with symptoms of immune dysregulation and a mild bleeding tendency, caused by defective actin polymerization in the immune cells, in a 7-year-old male patient born as the first child of consanguineous, healthy Moroccan parents.…”
Section: Combined Immunodeficiency With Severe Inflammation and Allermentioning
confidence: 99%
“…3 The activities of nucleation-promoting factors for actin polymerization are mostly regulated by signaltransduction pathways, one of which involves the activation by the Rho-family guanosine triphosphatases CDC42 and RAC2, and the Wiskott-Aldrich Syndrome protein (WASP) family as the intermediary Arp2/3 activator that can control actin assembly downstream of these small guanosine triphosphatases. 4,5 Here we describe the first human genetic defect in a component of the Arp2/3 complex itself. The ARPC1B mutation results in a combined immunodeficiency with symptoms of immune dysregulation and a mild bleeding tendency, caused by defective actin polymerization in the immune cells, in a 7-year-old male patient born as the first child of consanguineous, healthy Moroccan parents.…”
Section: Combined Immunodeficiency With Severe Inflammation and Allermentioning
confidence: 99%
“…Through these studies, CRS with nasal polyps (CRSwNP) has been recognized as an inflammatory subtype characterized by eosinophilic inflammation and a T-helper cell type 2 immunologic profile. [21][22][23] Although CRSwNP lacks the features of a classic infectious process, the precise role of bacteria and their byproducts in the promotion of nasal polyp-related inflammation remains unclear. 24 Recent findings from culture independent investigations of the sinonasal microbiome have offered new insights into the pathogenesis of CRS.…”
Section: And the European Positionmentioning
confidence: 99%
“…However the distinct lack of long‐term disease resolution following antimicrobial therapy, and in some cases surgery, suggests that additional factors are likely involved. Through these studies, CRS with nasal polyps (CRSwNP) has been recognized as an inflammatory subtype characterized by eosinophilic inflammation and a T‐helper cell type 2 immunologic profile . Although CRSwNP lacks the features of a classic infectious process, the precise role of bacteria and their byproducts in the promotion of nasal polyp‐related inflammation remains unclear …”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies examining P-gp function within sinonasal mucosa have shown that this function can regulate the secretion of type 2 helper T-cell (Th2)-associated cytokines in a concentrationdependent manner. [3][4][5] Epithelial P-gp protein further has been shown to be overexpressed in patients with chronic rhinosinusitis with nasal polyps (CRSwNP), [6][7][8] suggesting a key role in the immunopathophysiology of Th2-mediated sinonasal inflammation. This role was confirmed by a recent, double-blind randomized placebo-controlled clinical trial (DBRCT) demonstrating that P-gp inhibition was as effective as oral steroids and biologic agents in controlling both subjective and objective measures of CRSwNP.…”
Section: Introductionmentioning
confidence: 99%